Low-Cost DC Motor Design for Embedded Systems in Smart Applications - Patel, Arjun (Journal Innovations Computer Science, 2025)
The rapid growth of embedded systems demands reliable, efficient, and affordable actuators for smart applications such as home automation and IoT. This study develops a low-cost DC motor based on fundamental electromagnetic principles, finite element analysis (FEA), and Arduino-based PWM control. The motor is constructed from simple materials like copper wire, iron core, and neodymium magnets, with a production cost under five US dollars per unit. Experimental results demonstrate efficiency up to 35% at 165 RPM with a 100-turn coil configuration and a 0.4 Tesla magnetic field. FEA is used to validate the design and identify optimal configurations, while PWM control enables precise speed and torque regulation. The motor is integrated into a smart curtain prototype using MQTT, which automatically adjusts curtain position based on light sensor input, proving the motor’s compatibility with modern automation systems. Experimental findings reveal that increasing coil turns and magnetic field strength significantly improves torque, speed, and mechanical stability. This motor offers a cost-effective solution suitable for educational, research, and commercial applications in resource-constrained environments. The study also opens avenues for future brushless motor development and AI-based adaptive control to further enhance performance. By combining mechanical simplicity with electronic sophistication, this motor presents an optimal alternative for embedded systems prioritizing efficiency and affordability. This approach supports the democratization of automation technology, especially in developing countries and educational institutions with limited budgets.